The interrelation between the perception and production of English monophthongs by speakers of Iraqi Arabic - Al Abdely, Ammar A.; Yap, Ngee Thai (Universiti Putra Malaysia Press, 2016)
The assumption that performance in second language (L2) speech perception and speech production is aligned has received much debate in L2 research. Theoretical models such as the Motor Theory (MT) and Speech Learning Model (SLM) have described the relation between these two processes based on the assumption that speech is perceived with reference to how it is produced and speech production is in turn influenced by how well speech contrast is perceptible to the second-language learner. The present study aims to investigate this relation with regard to Iraqi learners' perception and production of English vowels, focussing on the role of L1 interference and English proficiency level in shaping this relation. The results of the present study showed that accurate perception may not necessarily be a prerequisite for accurate production especially for EFL learners at the elementary level. Perception and production score means were significantly different, revealing an asymmetrical relation between the two processes. The results showed that speech production of L2 learners at the elementary level exceeded their ability in speech perception. However, for the other three proficiency levels, perception and production seemed to develop in synchrony. The level of difficulty encountered in the perception and production tasks could be attributed to L1 interference, since the vowels that were better produced than perceived are all found in the L1 vowel system, while the only vowel that was better perceived is not in the L1 vowel system.